Ginger (Zingiber Officinale Roscoe) Prevents Morphine-Induced Addictive Behaviors in Conditioned Place Preference Test in Rats - Shima Torkzadeh-Mahani; Sima Nasri; Saeed Esmaeili-Mahani (Addiction and Health, 2014)
Background: Consumption of chronic morphine induces neuro-inflammation and addictive seeking behavior. Ginger (Zingiber Officinale Roscoe), a well-known spice plant, has been used traditionally in the treatment of a wide variety of ailments. It has been shown that ginger has anti-inflammatory, anti-oxidative and antinociceptive properties. However, its influences on morphine-induced addictive behaviors have not yet been clarified. Methods: For conditioning to the morphine, the male Wistar rats received morphine (12 mg/kg intraperitoneally or i.p.) for 6 consecutive days and treatment groups were given different doses of ginger (25, 50 and 100 mg/kg intragastrically or i.g.) 30 min before morphine injection. For investigating addictive seeking behavior, conditioned place preference test (CPP) was used. Findings: Our result demonstrated that injection of morphine for 6 days induces dependency to morphine and creates addictive seeking behavior and ginger (100 mg/kg) could decrease time spend in conditioning box (addictive seeking behavior). Conclusion: The data indicated that ginger extract has a potential anti-addictive property against chronic usage of morphine.